2022
DOI: 10.3389/fmed.2022.944547
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Non-invasive Model to Predict Liver Histological Lesions in Chronic Hepatitis B Patients With Persistently Normal Alanine Aminotransferase and Detectable Viremia

Abstract: BackgroundA critical and controversial issue is whether antiviral therapy should be recommended in chronic hepatitis B virus (HBV) infection patients with persistently normal alanine aminotransferase (PNALT) and detectable HBV DNA. The study aimed to develop a non-invasive model for predicting significant liver histological changes (SLHC), which is the histological indication for antiviral therapy in chronic hepatitis B (CHB) patients with PNALT and detectable HBV DNA.Methods398 chronic HBV infection patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have demonstrated the accuracy with which non-invasive models, such as the FIB-4 and APRI indices [ 45 ], the ALT, Age, PLT, and LS model [ 48 ], the AAR, API, APRI, KING, Zeugma scores, and Hudu’s score [ 49 , 50 ], can evaluate liver histology and forecast substantial liver injury. It has been discovered that these non-invasive models exhibit remarkable accuracy, with values of the area under the curve ranging from 0.595 to 0.870 [ 51 , 52 ]. They can assist in determining whether antiviral therapy is necessary without requiring an invasive biopsy of the liver, which carries some risk.…”
Section: Prognostic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated the accuracy with which non-invasive models, such as the FIB-4 and APRI indices [ 45 ], the ALT, Age, PLT, and LS model [ 48 ], the AAR, API, APRI, KING, Zeugma scores, and Hudu’s score [ 49 , 50 ], can evaluate liver histology and forecast substantial liver injury. It has been discovered that these non-invasive models exhibit remarkable accuracy, with values of the area under the curve ranging from 0.595 to 0.870 [ 51 , 52 ]. They can assist in determining whether antiviral therapy is necessary without requiring an invasive biopsy of the liver, which carries some risk.…”
Section: Prognostic Markersmentioning
confidence: 99%
“…The conventional approach to determining the prognosis of CHB infection involves liver biopsy; however, there are several drawbacks to this method, including cost, potential problems, and invasiveness [ 45 , 48 , 49 ]. An alternate method that has benefits including becoming kinder to the body, safer, and more economical is to use non-invasive diagnostics [ 51 , 52 ]. To forecast liver histological alterations and fibrosis in CHB patients, several non-invasive models were created utilising various indicators [ 53 ], [ 54 ], [ 55 ].…”
Section: Prognostic Markersmentioning
confidence: 99%